Analisis Risiko Kesehatan Paparan Gas Nitrogen Dioksida (No2) pada Petugas Parkir di Basement Plaza Andalas - Riviwanto, Muchsin; Sani, Fajar Mavira (Politeknik Kesehatan Tanjungkarang, 2017)
Nitrogen dioxide (NO2)is a gas that is poisonous reddish brown and very pungent smell like sour nitrat. Emission from vehicle of concentration NO2 reach 78,8 ppm, this result means so dangerous to health, especially that emission in door, like basement. The porpuse this study was to analyze the health risks of nitrogen dioxide exposure to the parking attendant Plaza Andalas Basement. This research is a descriptive study using a health risk analysis environmental method. Analyze exposure of nitrogen dioxide on the parking attendant Plaza Andalas Basement. Samples are conditioned at Plaza Andalas Basement taken as many as five measurement points within two days, and the parking attendant amounted to 15 people. Analysis of data using univariat. Analysis of data presented in the form of a frequency distribution table and then narrated. Based on the research result the average concentration of nitrogen dioxide is 13,53 µg/Nm3, analysis of dose-respons of nitrogen dioxide is 0,02 mg/kg/day for noncarcinogen effect. The average intake of exposure nitrogen dioxide to parking attendant is 0,00006184 mg/kg/day, with an average maximum concentration acceptable of nitrogen dioxide has worked is 13,2152 mg/Nm3. All parking attendant Plaza Andalas Basement is not at risk of expousure of nitrogen dioxide. From the research result the conclusion is all parking attendant is not at risk expousure of nitrogen dioxide. Recommended to the manager of Plaza Andalas Basment to increase exhaust and to the presence of nitrogen dioxide gas should keep an eye of the Plaza Andalas Basement so as not to increase.